Penggunaan Alat Peraga Kartu Domino terhadap Hasil Belajar Matematika - Maya Nurfitriyanti; Witri Lestari (Universitas Indraprasta PGRI, 2016)
Using Domino Card prop on Mathematics Achievement. This research aims to determine the effect of using domino card prop on mathematics achievement. This research was conducted in one of the public elementary schools in Depok. The number of samples in this research as many as 40 students were divided into two groups. 20 students belong to experiment group that taught using domino card prop, while 20 other students included in the control group is taught using conventional teaching aids. Sampling technique used in this research is a random sampling tecnique, where each population has the same chance to be sampled. The analysis technique used in this research is descriptive statistics, which states that the results are the average results of mathematics on higher grade than the control group. In this research, also conducted the data analysis prerequisite test is a test of normality and homogeneity test. Of the prerequisite test on the result that both the data were normally distributed and homogeneous. Test data analysis used with the result that the t test is greater than t table which means that there is significant effect of using domino card prop on mathematics achievement.